East Asia Economic Integration: Past, Present and Future Prospects - Lee, Kun Woo (2010)
This research argues that although the importance of economic integration in East Asia is acknowledged, there is scant understanding of the subject. As a result, this study has formulated an institutional framework to assist a systematic explanation of the subject. Thus, the framework will be developed by embracing Krugman’s (1993) New Trade Theory with respect to the trend of regional economic integration globally, hence classifying the trend and reaction towards it under the dimensions of intra-regional production links, FDI inflows and government policies. The framework is then applied to examine the wave of current economic integration in East Asia. This will be achieved by examining the applicability of the framework as well as adding to our overall understanding of East Asian economic integration. As a result, the case study finds that the institutional framework developed in this research proved to be a useful guide, and the dimensions of intra-regional production links and government policies were found to have facilitated regional economic interdependence. This explorative categorisation method is expected to allow future researchers to carry on a systematic analysis of the effects of economic integration on countries. Finally, the study finishes with describing limitations of the research and recommendations for future studies.